Pengaruh Kompetensi, Program Keselamatan dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan Divisi Gedung Pada PT Hutama Karya (Persero) - Satriya Permana Harnawan; Lukman Hakim (Ilmu Ekonomi Manajemen dan Akuntansi, 2020)
The more intense competition in the field of construction, making the company needs to pay attention to human factors in order to survive and compete with the labor in the field of construction services is to increase work productivity. If the employee productivity is low then the results of his work will decrease so that the target company is not achieved and the company is unable to compete. This research conducted in PT Hutama Karya. The purpose of this study is to determine the effect of competence and safety and health programs on employee work productivity. This research is associative research with causality relationship and quantitative approach by using linear regression analysis technique assisted with SPSS version 20 program. Competence and occupational safety and health variables have a positive and significant effect on employee work productivity in employees from PT Hutama Karya Divisi Gedung. Significant influence is evidenced from the F value = 15.214 which means significant because greater than F table = 2.794. With a significance level of 0.000 which is much smaller than (0.05). Then the competence variable indicates that t value t table (3.562 2.010) or has a significance level of 0.001 (less than 0.05). And the occupational safety and health program (X2) shows that t value t table (2.258 2.010) or has a significance level of 0.028 (less than 0.05). Both of these variables each have a partial effect on employee productivity.Keywords: Competence, Occupational Safety, Health Program, Work Productivity